2019
DOI: 10.1249/jes.0000000000000185
|View full text |Cite
|
Sign up to set email alerts
|

mHealth Interventions for Exercise and Risk Factor Modification in Cardiovascular Disease

Abstract: A digital platform hosting a suite of evidence-based interventions could promote exercise and lifestyle risk factor modification for the secondary prevention of heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Even though we were unable to demonstrate the superiority of mHealth promoting physical activity and lifestyle interventions over usual care (in-person consultations with clinicians) owing to the scarcity of studies comparing data between control and intervention groups, our results showed that mHealth interventions are effective in improving cardiometabolic risk. Our data regarding the effects of interventions based on mHealth technologies are similar to those involving traditional care [ 42 ], suggesting that they could represent an alternative treatment strategy because of their acceptability, scalability, cost-effectiveness, customization, and ability to send time-sensitive messages with an “always on” device [ 43 ]. Moreover, mHealth physical activity interventions reduce in-person health provider time and increase self-care by enabling patients to manage their progress [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though we were unable to demonstrate the superiority of mHealth promoting physical activity and lifestyle interventions over usual care (in-person consultations with clinicians) owing to the scarcity of studies comparing data between control and intervention groups, our results showed that mHealth interventions are effective in improving cardiometabolic risk. Our data regarding the effects of interventions based on mHealth technologies are similar to those involving traditional care [ 42 ], suggesting that they could represent an alternative treatment strategy because of their acceptability, scalability, cost-effectiveness, customization, and ability to send time-sensitive messages with an “always on” device [ 43 ]. Moreover, mHealth physical activity interventions reduce in-person health provider time and increase self-care by enabling patients to manage their progress [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be done by either assisting cancer survivors in selecting applications from a library based on a declaration of specific content as described by Short et al [ 26 ] or by designing applications [ 25 ] that can adapt to the cancer survivor’s preferences and readiness level. By hosting a variety of existing applications [ 46 ] selected to cover the various readiness levels and preferences, more advanced digital platforms could also serve to aid adoption of technology at any stage of the cancer trajectory. Some platform applications should support social interaction, while others should aim to provide an underlying understanding of the activities and how they contribute to the cancer survivors’ health, increasing their ability to manage their condition.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is an effective strategy for reducing blood pressure in the general population; however, it is not known whether exercise would have a comparable benefit in people with moderate to advanced chronic kidney disease and hypertension [15]. Recent studies showed that exercise and lifestyle risk factor management are critical for the secondary prevention of cardiovascular disease but are poorly adhered to [16]. Elevated levels of highdensity lipoprotein cholesterol (HDL-C) have been associated with a decreased risk of coronary heart disease (CHD).…”
Section: Discussion:-mentioning
confidence: 99%